Doing the plastic fantastic: 'artificial' adventure and older adult climbers. Issue 2 (3rd April 2019) - Hickman, Mark; Stokes, Peter; Beard, Colin; Inkster, Allison
ABSTRACT: The aim of this article is to determine the perceptions and experiences of climbing at artificial climbing walls (ACWs) as undertaken by a cohort of 'young-old' people (approximately 65–75 years). The engagement of older people in outdoor activities and adventure is an evolving topic; however, as part of this development, little has been written on the use of ACWs. Methodologically, the research employed in-depth semi-structured focus groups and interviews with a purposive convenience sample of six recreational climbers, subsequently expanded to ten through snowball technique. Both sexes were equally represented. Manual thematic analysis identified two key motifs: ACWs and the notion of adventure, and ACWs and the potential for learning. The findings point at what constitutes 'real' adventure for this group of older adults; the shifting nature of 'old age'; the significance of self-awareness; and the role of reflexivity and physical activity in the construction of a 'successful' old age.